Community Health Nursing in Iran: A Review of Challenges and Solutions (An Integrative Review) - Hosseinnejad, Aazam; Rassouli, Maryam; Jahani, Simin; Elahi, Nasrin; Molavynejad, Shahram (Frontiers in Public Health, 2022)
Background and Objective: In recent decades, nursing has witnessed many changes in Iran. Despite the numerous advances in nursing, the health system faces many challenges in community health nursing. This study aims to review the challenges in community health nursing in Iran and provide an evidence-based solution as well. Materials and Methods: This article is an integrated review of the literature regarding the challenges in community health nursing published between 2000 and 2021 in the databases Scopus, Medline, Cochrane Database of Systematic Reviews, Science Direct, Google Scholar, Scientific Information Database (SID). After performing searches, 20 articles were selected and studied. Data analysis was done using Russell approach (2005). Findings: The results of this study were summarized in 6 themes consisting of challenges in community health nursing education, practical challenges in community health nursing, policy-making challenges in community health nursing, management challenges in community health nursing, and infrastructural and cultural challenges. Solutions were also proposed to address each of the above issue. Conclusions: The results of the study showed that although diverse challenges exist in community health nursing in Iran, considering that community health nurses play an important role in providing primary health care and community-based care, it is necessary to reform the structure of the health system, to create a position for the practice of community health nurses and to reform nursing students’ education using a community-based approach in order to address many of these challenges.